Observation of Iron Status among Pregnant Women (The Planet, 2023)
Introduction: The observation of iron status among pregnant women in rural Bangladesh is an important issue as it can have a significant impact on the health and well-being of both the mother and the child. Iron deficiency anemia is a common problem among pregnant women in developing countries and can lead to a variety of complications during pregnancy, delivery, and postpartum. Aim of the study: The aim of the study was to observe the general iron status of pregnant women in Rural Bangladesh. Methods& Materials: This prospective observational study was conducted at the Department of Gynaecology, Sonargaon Seba General Hospital, Sonargaon, Narayanganj, Bangladesh. The study duration was 1 year, during which period, data from a total of 113 pregnant women were collected who had been admitted to the study hospital. Results: The study recruited 113 pregnant women in rural Bangladesh, the majority of them were between the ages of 15-25 and were housewives. The results showed that 77.88% had low hemoglobin levels, 55.75% had low ferritin levels, 67.26% were multi-gravida, the mean age was 22.99 years, the mean weight was 58.53 kg, the mean hemoglobin level was 10.824 mg/dl, and mean ferritin level was 17.35 mg/dl.Conclusion: The study found that the majority of the participants had low Hemoglobin and ferritin levels, indicating a concern for iron deficiency anemia. The results suggest that interventions, such as iron supplementation and nutrition education, are needed to improve the iron status of pregnant women in this population.
Keywords: Pregnancy; Childbirth; Ferritin; Iron; Anemia